MODUL PEMBELAJARAN BATIK KELAS IX SMK NEGERI 8 PADANG - Aryati, Yulia; Efi, Agusti; Yusmerita, Yusmerita (Journal of Home Economics and Tourism, 2014)
This study begins from the goal of national education system on improving the quality of learning through learning outcomes. SMKN 9 Padang including one of the schools that still realy on textbooks in the learning process of batic. Pre-study observations show that the learning batic has not met expectations. This is likely because the students do not have a background in terms of making batic.2Science is developed to introduce the module as one of the teaching materials that can improve student learning outcomes effectively and efficiently. This research was conducted with the aim of : 1) produce a valid batik learning modules, practically, and efficient, 2) develop a learning module on batic material for secondary vocational schools.This type of research is the research and development or development methods, namely designing and making batic learning modules, and then test the validity, practicalities and effectiveness. Each test is done, there is validation sheet stating valid or not. Data analysis technique consists of analyzing the validity, practicalities and effectiveness. The questionnaire contains about practicality, activities and student motivation. Questionnaire data were analyzed using a Likert scale. Research object is a class XI student SMKN 8 Padang.The result based on data obtained show that the learning module batic produced in a valid category, practical and effective both in terms of the feasibility of the module content, language of modules, graph and presentation of module. It was concluded that the learning module batic worthy to serve as one of the reference material in the development of textile craft module specifically about learning batic.Keyword : Batic Learning Modules